Ceramsite with core-shell structure as well as preparation method and application of ceramsite
Through the combination of biochar core and steel slag powder and glass powder shell, lightweight and high-strength core-shell structural ceramics are prepared, which solves the problem of high density of burn-free ceramics, and realizes efficient utilization of carbon fixation, steel slag, and waste glass, and is suitable for the field of building materials.
Patent Information
- Application Number
- CN202510691149.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-27
- Publication Date
- 2025-08-22
AI Technical Summary
The existing sintered ceramics have a high density, which is difficult to meet the density and strength requirements of lightweight concrete aggregates. In addition, traditional sintered ceramics have high energy consumption and do not meet the requirements of green and low-carbon development.
Biochar is used as the core core, steel slag powder and glass powder are used as the raw materials for the shell, and mixed and cured and formed through a rotary granulator to form core-shell structural ceramic granules. The steel slag powder and glass powder in the shell are synergistically excited to prepare ceramic granules with moderate density and high strength.
It realizes the preparation of lightweight and high-strength ceramic granules, solves the utilization problems of steel slag and waste glass, improves carbon sequestration efficiency, and meets the needs of building materials for lightweight, high-performance, green and environmental protection.
Smart Images

Figure CN120518344A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid waste utilization, and in particular to a core-shell structured ceramsite and a preparation method and application thereof. Background Art
[0002] Ceramic aggregate is a man-made lightweight aggregate with good thermal insulation, fire resistance and durability, and is widely used in the field of building materials. Depending on the preparation process, ceramsite can be divided into sintered ceramsite and unfired ceramsite. Traditional sintered ceramsite needs to be baked and formed at high temperature, which consumes a lot of energy and has high carbon emissions, and does not meet the requirements of green and low-carbon development. In contrast, unfired ceramsite is made by mixing inorganic gelling materials such as fly ash, clay, cement or alkali-activated materials with a foaming agent, and then undergoing conventional single-stage or multi-stage granulation and low-temperature curing to form it. It has the advantages of low energy consumption and simple process. However, the overall density of existing unfired ceramsite is relatively high (≥900kg / m 3 ), it is difficult to meet the dual requirements of density and strength of lightweight concrete aggregate, which limits its application in the construction field. Summary of the Invention
[0003] The purpose of the present invention is to provide a core-shell structure ceramsite and a preparation method and application thereof. The core-shell structure ceramsite provided by the present invention has moderate density, high strength and is green and environmentally friendly.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a core-shell structured ceramsite, comprising a core and a shell wrapped around the surface of the core, wherein the core is biochar, and raw materials for preparing the shell include steel slag powder, glass powder and cement, wherein the total mass content of steel slag powder and glass powder in the raw materials for preparing the shell is greater than 50%.
[0006] Preferably, the core-shell structure ceramsite has a cylinder compressive strength of 4.8 to 10.9 MPa and a bulk density of <900 kg / m 3 .
[0007] Preferably, the steel slag powder has a particle size D90 ≤ 20 μm, a free calcium oxide content of 0 to 6 wt%, and a calcium hydroxide content of 0 to 8 wt%;
[0008] The particle size D90 of the glass powder is ≤45 μm, and the glass powder is obtained by grinding waste glass;
[0009] The cement is ordinary Portland cement.
[0010] Preferably, the thickness of the shell is 1 to 2 mm; the particle size of the biochar is 2.36 to 4.75 mm, and the bulk density is 300 to 600 kg / m 3 , the cylinder pressure strength is 1.5~5MPa.
[0011] Preferably, the mass ratio of the steel slag powder to the glass powder is 3:6-8, the mass ratio of the total mass of the steel slag powder and the glass powder to the cement is 7-9:1-3; and the volume ratio of the raw materials for preparing the shell to biochar is 0.5-2:1.
[0012] The present invention provides a method for preparing the core-shell structure ceramsite described in the above technical solution, comprising the following steps:
[0013] Firstly mixing steel slag powder, glass powder and cement to obtain shell raw materials;
[0014] performing a second mixing of the shell raw material and biochar to obtain a biochar mixture;
[0015] The biochar mixture is mixed with water for a third time to obtain prefabricated ceramsite;
[0016] The prefabricated ceramsite is cured and formed to obtain the core-shell structure ceramsite.
[0017] Preferably, the biochar includes completely dry biochar or saturated surface dry biochar; when the biochar is completely dry biochar, the mass ratio of the water to the shell raw material is 0.2 to 0.4:1; when the biochar is saturated surface dry biochar, the mass ratio of the total mass of the water and the water in the saturated surface dry biochar to the shell raw material is 0.2 to 0.4:1.
[0018] Preferably, the first mixing, the second mixing and the third mixing are carried out in a rotary granulator; the conditions for the first mixing include: a rotation rate of 32 to 48 r / min, a rotation angle of 40 to 45°, and a mixing time of 4 to 6 min; the conditions for the second mixing include: a rotation rate of 32 to 48 r / min, a rotation angle of 40 to 45°, and a mixing time of 1.5 to 2.5 min; the conditions for the third mixing include: a rotation rate of 16 to 24 r / min, a rotation angle of 40 to 45°, and a mixing time of 20 to 30 min.
[0019] Preferably, the curing and molding temperature is 80° C. and the time is 3 days.
[0020] The present invention provides the use of the core-shell structure ceramsite described in the above technical solution or the core-shell structure ceramsite prepared by the preparation method described in the above technical solution in lightweight carbon-fixing aggregate concrete.
[0021] The present invention provides a core-shell ceramsite comprising a core and a shell wrapped around the core. The core is biochar, and the shell is made from raw materials including steel slag powder, glass powder, and cement, with the total mass content of the steel slag powder and glass powder exceeding 50%. The present invention uses biochar as the core to achieve carbon sequestration, while simultaneously utilizing a large amount of solid waste (steel slag powder and glass powder) and cement to produce the shell through a synergistic effect. The resulting core-shell ceramsite has the advantages of high carbon sequestration efficiency, high solid waste utilization, moderate density, high cylinder pressure strength, and environmental friendliness.
[0022] Furthermore, the steel slag powder and glass powder in the present invention can be derived from solid waste steel slag and waste glass, which solves the problem of effective utilization of steel slag and waste glass, while overcoming the defects of existing ceramsite in density and strength, and producing lightweight and high-strength core-shell structure ceramsite with density and strength that meet the requirements, thereby meeting the demand for lightweight, high-performance, green and environmentally friendly building materials in the construction field. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a flow chart of preparing core-shell structure ceramsite in an embodiment of the present invention;
[0024] Figure 2 XRD patterns of steel slag powder, glass powder, OPC and biochar;
[0025] Figure 3 The particle size distribution diagram of steel slag powder, glass powder and OPC;
[0026] Figure 4 is the 24h water absorption curve of biochar;
[0027] Figure 5 The graph is a relationship between the yield and particle size of the core-shell structure ceramsite in Examples 1 to 8 and Comparative Examples 1 to 3;
[0028] Figure 6 The figure shows the test results of cylinder compressive strength and bulk density of core-shell structure ceramsite;
[0029] Figure 7 This is the water absorption test result of core-shell structure ceramsite;
[0030] Figure 8 The cross-sectional physical image and three-dimensional scanning image of the core-shell structure ceramsite prepared in Example 1;
[0031] Figure 9 This is a diagram of the interface between the core and shell of the core-shell structured ceramsite prepared in Example 1;
[0032] Figure 10 This is a physical picture of the core-shell structure ceramsite prepared in Example 1;
[0033] Figure 11This is a physical picture of the core-shell structure ceramsite prepared in Example 2;
[0034] Figure 12 This is a physical picture of the core-shell structure ceramsite prepared in Example 3;
[0035] Figure 13 This is a physical picture of the core-shell structure ceramsite prepared in Example 4;
[0036] Figure 14 This is a physical picture of the core-shell structure ceramsite prepared in Example 5;
[0037] Figure 15 This is a physical picture of the core-shell structure ceramsite prepared in Example 6. DETAILED DESCRIPTION
[0038] The present invention provides a core-shell structured ceramsite, comprising a core and a shell wrapped around the surface of the core, wherein the core is biochar, and raw materials for preparing the shell include steel slag powder, glass powder and cement, wherein the total mass content of steel slag powder and glass powder in the raw materials for preparing the shell is greater than 50%.
[0039] The core-shell structure ceramsite provided by the present invention adopts solid waste glass powder and steel slag powder to prepare the shell and biochar as the core. The coordinated excitation effect of glass powder and steel slag powder can effectively improve the activity of the two solid waste materials. The lightweight and high-carbon biochar helps to reduce the density of the core-shell structure ceramsite, and also improves the carbon fixation efficiency of the core-shell structure ceramsite, thereby meeting the demand for lightweight, high-performance, green and environmentally friendly building materials in the construction field, solving the problem of high energy consumption of sintered ceramsite relying on high-temperature calcination in the related art, and solving the problem that the unfired ceramsite does not need to be sintered but has a large bulk density and is difficult to meet the lightweight demand. In addition, in the current industrial and building materials field, steel slag and waste glass are used as solid wastes, because they have poor stability and low activity as cementitious materials alone, resulting in their utilization rate being at a low level. The accumulation of large amounts of steel slag and waste glass not only occupies precious land resources, but also causes a serious waste of resources. Although biochar is a common carbon-fixing material in the civil engineering field, when biochar is added to concrete in large quantities as a cementitious material and aggregate, due to its high porosity and high water absorption rate, it will cause a series of problems such as reduced strength and durability. This makes its content in concrete strictly limited, and it can usually only be maintained at less than 5%, resulting in difficulty in significantly improving the carbon fixation efficiency and being unable to meet the growing demand for carbon fixation and the requirement for high performance of building materials. The present invention uses biochar as the core, and compounding steel slag powder with glass powder to prepare core-shell structure ceramsite. Using this core-shell structure ceramsite as an aggregate in concrete can effectively increase the volume content of biochar in concrete (the volume content can be increased to 25-36%), greatly increasing the carbon fixation efficiency of concrete. The core-shell structure ceramsite of the present invention is described in detail below.
[0040] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art or are prepared using methods well known to those skilled in the art.
[0041] The core-shell structure ceramsite provided by the present invention includes a core, and the core is biochar. As an embodiment of the present invention, the particle size of the biochar can be 2.36 to 4.75 mm; in the embodiment of the present invention, a square hole sieve is specifically used for screening to obtain biochar in the above particle size range. As an embodiment of the present invention, the 1h water absorption rate of the biochar can be 33%; the cylinder pressure strength of the biochar can be 1.5 to 5 MPa, specifically 1.7 MPa, and the bulk density can be 300 to 600 kg / m 3 , specifically 311kg / m 3 As an embodiment of the present invention, the biochar can be specifically bamboo biochar. The bamboo biochar used in the examples of the present invention was specifically purchased from Henan Lize Environmental Protection Technology Co., Ltd.
[0042] The core-shell ceramsite provided by the present invention includes a shell wrapped around the surface of the core, and the raw materials for preparing the shell include steel slag powder, glass powder and cement. The total mass content of steel slag powder and glass powder in the raw materials for preparing the shell is greater than 50%. As an embodiment of the present invention, the thickness of the shell can be 1 to 2 mm. As an embodiment of the present invention, the mass ratio of the steel slag powder to the glass powder can be 3:6 to 8, specifically 3:7; the mass ratio of the total mass of the steel slag powder and glass powder to cement can be 7 to 9:1 to 3, specifically 7:3. As an embodiment of the present invention, the volume ratio of the raw materials for preparing the shell to biochar is 0.5 to 2:1, specifically 0.8:1, 1.2:1 or 1.8:1.
[0043] In one embodiment of the present invention, the steel slag powder has a particle size D90 ≤ 20 μm; the steel slag powder may be obtained by grinding steel slag. In this embodiment, the steel slag powder has a particle size D10 of 0.83 μm, a particle size D50 of 4.08 μm, and a particle size D90 of 17.20 μm. The steel slag powder may have a free calcium oxide content of 0 to 6 wt%, and a calcium hydroxide content of 0 to 8 wt%. The chemical composition of the steel slag powder is specifically shown in Table 1 of Example 1 and is not further described here.
[0044] In one embodiment of the present invention, the glass powder has a particle size D90 ≤ 45 μm; the glass powder may be ground from waste glass. In this embodiment, the glass powder has a particle size D10 of 1.34 μm, a particle size D50 of 9.88 μm, and a particle size D90 of 43.56 μm. The chemical composition of the glass powder is as shown in Table 1 of Example 1 and is not further described here.
[0045] As one embodiment of the present invention, the cement can be ordinary Portland cement (OPC), specifically P·O 42.5 type ordinary Portland cement. The ordinary Portland cement used in the embodiment of the present invention is specifically purchased from Anhui Conch Cement Co., Ltd., and the model is P·O 42.5. In the embodiment of the present invention, the particle size D10 of the ordinary Portland cement is specifically 0.98 μm, D50 is specifically 5.17 μm, and D90 is specifically 16.73 μm; the chemical composition of the ordinary Portland cement is specifically shown in Table 1 in Example 1, and will not be repeated here.
[0046] As an embodiment of the present invention, the cylinder compressive strength of the core-shell structure ceramsite can be 4.8 to 10.9 MPa, specifically 4.8 MPa, 5.1 MPa, 5.8 MPa, 6.5 MPa, 7.7 MPa, 9.4 MPa, 10.3 MPa or 10.9 MPa; the bulk density is less than 900 kg / m 3 , further can be 650~850kg / m 3 , specifically 658.7kg / m 3 、682.1kg / m 3 、686.6kg / m 3 、688.2kg / m 3 、771.2kg / m 3 、786.4kg / m 3 、802.6kg / m 3 or 817.0kg / m 3 As an embodiment of the present invention, the 1h water absorption rate of the core-shell structure ceramsite can be 16.1% to 26.2%, specifically 16.1%, 18.0%, 18.1%, 21.3%, 21.7%, 22.4%, 23.4% or 26.2%.
[0047] The present invention provides a method for preparing the core-shell structure ceramsite described in the above technical solution, comprising the following steps:
[0048] Firstly mixing steel slag powder, glass powder and cement to obtain shell raw materials;
[0049] performing a second mixing of the shell raw material and biochar to obtain a biochar mixture;
[0050] The biochar mixture is mixed with water for a third time to obtain prefabricated ceramsite;
[0051] The prefabricated ceramsite is cured and formed to obtain the core-shell structure ceramsite.
[0052] As one embodiment of the present invention, the first mixing, the second mixing, and the third mixing can be performed in a rotary granulator. As one embodiment of the present invention, the conditions for the first mixing include: a rotation rate of 32 to 48 r / min, specifically 40 r / min; a rotation angle of 40° to 45°, specifically 42°; and a mixing time of 4 to 6 minutes, specifically 5 minutes.
[0053] As one embodiment of the present invention, the biochar can be used in a manner including completely dried biochar or saturated surface-dried biochar. The completely dried biochar specifically refers to biochar fully dried at room temperature (25°C), and the saturated surface-dried biochar specifically refers to biochar fully absorbing water at room temperature and atmospheric pressure (101.325kPa) for 1 hour. As one embodiment of the present invention, the second mixing conditions include: a rotation rate of 32 to 48 rpm, specifically 40 rpm; a rotation angle of 40° to 45°, specifically 42°; and a mixing time of 1.5 to 2.5 minutes, specifically 2 minutes.
[0054] As one embodiment of the present invention, when the biochar is completely dry, the mass ratio of water to the shell raw material can be 0.2 to 0.4:1, specifically 0.2 to 0.3:1; when the biochar is saturated surface-dried biochar, the mass ratio of the total mass of water and the water in the saturated surface-dried biochar to the shell raw material can be 0.2 to 0.4:1, specifically 0.2 to 0.3:1. In the embodiments of the present invention, controlling the amount of water within the above range can act as a binder, which is beneficial for promoting the synergistic activation and full hydration of steel slag powder, glass powder, and cement binder in the shell, so that they adhere to the surface of the biochar and form a hard shell. As an embodiment of the present invention, the third mixing is specifically spraying water into the biochar mixture; during the water addition process, the rotation rate of the rotary granulator can be 16 to 24 r / min, specifically 20 r / min; the rotation angle can be 40° to 45°, specifically 42°; the water addition time can be 4 to 6 minutes, specifically 5 minutes; after the water is added, the rotation rate and rotation angle are preferably maintained unchanged and the rotation is continued for 20 to 30 minutes, specifically 25 minutes. In the embodiment of the present invention, the third mixing is carried out under the above conditions to form a powder shell on the surface of the biochar (the powder shell is formed by glass powder, steel slag powder and cement). After the water is added, the rotation rate and rotation angle are maintained unchanged and the rotation is continued, which can make the fluffy powder shell structure more compact and at the same time make the biochar and the powder shell tightly bonded, thereby obtaining prefabricated ceramsite.
[0055] After obtaining the prefabricated ceramsite, the present invention cures and shapes the prefabricated ceramsite to obtain the core-shell structure ceramsite. As one embodiment of the present invention, the curing and shaping temperature can be 80°C and the time can be 3 days. In the embodiment of the present invention, curing and shaping under the above conditions is conducive to the coordinated stimulation of steel slag powder and glass powder, generating sufficient strength and ultimately forming a hard shell. As one embodiment of the present invention, the curing and shaping can also include screening to obtain core-shell structure ceramsite of the desired particle size; in the embodiment of the present invention, the screening is specifically performed using a square hole sieve.
[0056] The core-shell structure ceramsite prepared by the method of the present invention is unfired ceramsite, can be used as lightweight aggregate, and has the advantages of high cylinder pressure strength and low cost.
[0057] The present invention provides the use of the core-shell structure ceramsite described in the above technical solution or the core-shell structure ceramsite prepared by the preparation method described in the above technical solution in lightweight carbon-fixing aggregate concrete. As one embodiment of the present invention, the core-shell structure ceramsite can be used as a lightweight carbon-fixing aggregate to prepare lightweight high-carbon-fixing concrete; the raw materials for preparing the lightweight high-carbon-fixing concrete include cement, core-shell structure ceramsite and water, and the mass percentage of the core-shell structure ceramsite to the mass percentage of the raw materials for preparing the lightweight high-carbon-fixing concrete is ≥50wt%, and can further be 50-60wt%, specifically 56.6wt%, 56.5wt% or 55.5wt%. As an embodiment of the present invention, the raw materials for preparing the lightweight high carbon fixation concrete may include 490 parts of cement, 500-550 parts of coarse aggregate, 300-320 parts of fine aggregate, and 160-180 parts of water, calculated by mass; the coarse aggregate may specifically be 519.48 parts, 544.44 parts, or 546.26 parts; the fine aggregate may specifically be 303.03 parts or 310.74 parts; the water may specifically be 170 parts; the coarse aggregate and the fine aggregate are obtained by sieving the core-shell structure ceramsite, specifically, the core-shell structure ceramsite is passed through a square hole sieve to obtain the coarse aggregate and the fine aggregate respectively; the aperture of the square hole sieve is 4.75 mm, that is, the coarse aggregate is a core-shell structure ceramsite with a particle size ≥4.75 mm, and the fine aggregate is a core-shell structure ceramsite with a particle size <4.75 mm. The lightweight high carbon fixation concrete of the present invention may specifically be C30 concrete; the density of the lightweight high carbon fixation concrete may be 1700-1800 kg / m 3 , meeting the density requirements of lightweight aggregate concrete in national standards.
[0058] Figure 1The flowchart of the preparation of core-shell structure ceramsite in the embodiment of the present invention is shown below. The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0059] The raw materials used in the following examples and comparative examples include steel slag powder, glass powder, ordinary Portland cement (OPC), and biochar, wherein the steel slag powder is obtained by grinding steel slag in a cement mill; the glass powder is obtained by grinding waste glass in a cement mill; the OPC is purchased from Anhui Conch Cement Co., Ltd., model P·O 42.5; and the biochar is specifically bamboo biochar, purchased from Henan Lize Environmental Protection Technology Co., Ltd.
[0060] The chemical compositions of the steel slag powder, glass powder and OPC are shown in Table 1.
[0061] Table 1 Main chemical compositions of steel slag powder, glass powder and OPC (wt%)
[0062] raw materials CaO <![CDATA[Fe2O3]]> <![CDATA[Na2O]]> <![CDATA[SiO2]]> <![CDATA[Al2O3]]> MgO <![CDATA[K2O]]> <![CDATA[P2O5]]> glass powder 8.88 0.64 14.64 70.59 2.32 1.57 0.66 0.07 OPC 56.23 3.13 0.18 26.04 8.03 1.70 0.74 0.14 Steel slag powder 43.25 19.96 0.13 17.42 4.03 5.99 0.04 2.20
[0063] The XRD patterns of the steel slag powder, glass powder, OPC and biochar are shown in Figure 2. Figure 2 As shown, the results show that the steel slag powder has a higher calcium oxide content and the glass powder has a higher silica content, forming an element complement to promote a coordinated excitation effect.
[0064] The biochar was sieved with a square mesh sieve to control its particle size to 2.36-4.75 mm; the particle sizes of the steel slag powder, glass powder and OPC are shown in Table 2 and Figure 3 As shown, Figure 3 The left side is the particle size distribution graph, and the right side is the cumulative distribution graph.
[0065] Table 2 Particle sizes of glass powder, steel slag powder and OPC
[0066] raw materials D10(μm) D50(μm) D90(μm) Steel slag powder 0.83 4.08 17.20 OPC 0.98 5.17 16.73 glass powder 1.34 9.88 43.56
[0067] The 24h water absorption curve of the biochar is as follows Figure 4 As shown, it can be seen that the 1h water absorption rate of the biochar is 33%; the cylinder pressure strength of the biochar is 1.7MPa.
[0068] The biochar with a particle size of 2.36 to 4.75 mm was placed in a vacuum drying oven and fully dried. After being sealed and cooled to room temperature, it was divided into two parts. One part was subjected to room temperature and atmospheric pressure conditions to absorb water for 1 hour to obtain saturated surface dry biochar (denoted as W) for use, and the other part was kept dry at room temperature to obtain completely dry biochar (denoted as D) for use.
[0069] Example 1
[0070] 490 g of glass powder, 210 g of steel slag powder and 300 g of OPC were placed in a rotary granulator and pre-mixed for 5 min at a rotation rate of 40 r / min and a rotation angle of 42° to obtain a shell raw material; saturated surface dry biochar was placed in a rotary granulator containing the shell raw material (the volume ratio of the shell raw material to the saturated surface dry biochar was 1.6:1), and mixed for 2 min at a rotation rate of 40 r / min and a rotation angle of 42° to obtain a biochar mixture; 143.5 g of water was evenly added to the rotary granulator containing the biochar mixture as a binder at a rotation rate of 20 r / min and a rotation angle of 42°, and the water content was 2.5%. The feeding time is 5 minutes, so that a powder shell is formed on the surface of the biochar (the powder shell is formed by glass powder, steel slag powder and OPC). After the water is added, the rotation rate and rotation angle are kept unchanged and the rotation is continued for 25 minutes to make the fluffy powder shell structure more compact and at the same time make the biochar and the powder shell tightly bonded to obtain prefabricated ceramsite with a powder shell thickness of 1 to 2 mm; the prefabricated ceramsite is cured and formed at a temperature of 80°C for 3 days, and then sieved through a square hole sieve with an aperture of 4.75 mm to obtain core-shell structure ceramsite (coarse aggregate) with a particle size of ≥4.75 mm and core-shell structure ceramsite (coarse aggregate) with a particle size of <4.75 mm, respectively.
[0071] The core-shell structure ceramsite prepared in this embodiment is recorded as 30%-W-1.6:1, where 30% represents the mass percentage of OPC in the shell raw material, W represents the use of saturated surface dry biochar, and 1.6:1 represents the volume ratio of the shell raw material to the saturated surface dry biochar.
[0072] Example 2
[0073] The method of Example 1 was used, except that the amount of each component added was specifically listed in Table 3.
[0074] Example 3
[0075] 490 g of glass powder, 210 g of steel slag powder and 300 g of OPC were placed in a rotary granulator and pre-mixed for 5 min at a rotation rate of 40 r / min and a rotation angle of 42° to obtain a shell raw material; completely dried biochar was placed in a rotary granulator containing the shell raw material (the volume ratio of the shell raw material to the completely dried biochar was 1.6:1) and mixed for 2 min at a rotation rate of 40 r / min and a rotation angle of 42° to obtain a biochar mixture; 200 g of water was evenly added to the rotary granulator containing the biochar mixture as a binder at a rotation rate of 20 r / min and a rotation angle of 42°, and the addition of water was 100 g / min. The feeding time is 5 minutes, so that a powder shell is formed on the surface of the biochar (the powder shell is formed by glass powder, steel slag powder and OPC). After the water is added, the rotation speed and rotation angle are kept unchanged and the rotation is continued for 25 minutes to make the fluffy powder shell structure more compact and at the same time make the biochar and the powder shell tightly bonded to obtain prefabricated ceramsite with a powder shell thickness of 1 to 2 mm; the prefabricated ceramsite is cured and formed at a temperature of 80° C. for 3 days, and then sieved through a square hole sieve with an aperture of 4.75 mm to obtain core-shell structure ceramsite (coarse aggregate) with a particle size of ≥4.75 mm and core-shell structure ceramsite (coarse aggregate) with a particle size of <4.75 mm, respectively.
[0076] The core-shell structure ceramsite prepared in this embodiment is recorded as 30%-D-1.6:1, where 30% represents the mass percentage of OPC in the shell raw material, D represents the use of completely dry biochar, and 1.6:1 represents the volume ratio of the shell raw material to the completely dry biochar.
[0077] Examples 4 to 8 and Comparative Examples 1 to 3
[0078] The method of Example 3 was used, except that the amount of each component added was specifically listed in Table 3.
[0079] Table 3 Formula of core-shell structure ceramsite in Examples 1 to 8 and Comparative Examples 1 to 3
[0080]
[0081]
[0082] Figure 5 The figure is a relationship diagram between the yield and particle size of the core-shell structure ceramsite in Examples 1 to 8 and Comparative Examples 1 to 3. The results show that the method of the present invention has a higher granulation efficiency and a higher yield of the core-shell structure ceramsite.
[0083] Test Example 1
[0084] This test case analyzes the various properties of core-shell ceramsite through indicators such as bulk density, cylinder pressure strength, 24h water absorption rate, and biochar ratio. The specific test methods for each indicator are as follows:
[0085] (1) Bulk density
[0086] Take the core-shell structure ceramsite and place it in a drying oven to dry to constant weight. Pour the dried core-shell structure ceramsite evenly from 50mm above the mouth of the capacity cylinder, allowing the sample to fall naturally without touching the capacity cylinder. After filling, make the sample above the mouth of the capacity cylinder into a cone. Then use a ruler to scrape it from the center to both sides along the edge of the capacity cylinder. Fill the concave parts of the surface with core-shell structure ceramsite with smaller particle size and weigh it. Calculate the bulk density according to formula I:
[0087] ρ bv =(m t -m v )×1000 / V Formula I;
[0088] ρ bv - Bulk density, in kilograms per cubic meter (kg / m 3 );
[0089] m t ——Total mass of the sample and the volumetric cylinder, in kilograms (kg);
[0090] m v ——The mass of the volumetric cylinder, in kilograms (kg);
[0091] V – the volume of the capacity cylinder, in liters (L).
[0092] (2) Cylinder pressure strength
[0093] Take the core-shell structure ceramsite as the sample, use the pressure cylinder to load the sample to the top of the cylinder mouth, place it on the vibration table and vibrate for 3s, then load the sample to the top of the cylinder mouth, place it on the vibration table and vibrate for 5s, and scrape the sample along the cylinder mouth. Install the guide cylinder and the punching die so that the lower scale line of the punching die is aligned with the upper edge of the guide cylinder. Place the pressure cylinder on the lower platen of the press, align it with the center of the platen, and apply the load at a uniform speed of 300N per second. When the punching die is pressed into the depth of 20mm, record the pressure value. Calculate the cylinder pressure strength according to formula II:
[0094] f a =(p1+p2) / F Formula II;
[0095] f a ——cylinder compressive strength, in megapascals (MPa);
[0096] p1——pressure value when the pressing depth is 20mm, unit is Newton (N);
[0097] p2——stamping die weight, in Newton (N);
[0098] F——pressure bearing area, unit is per cubic millimeter (mm 2 ).
[0099] (3) Water absorption
[0100] The core-shell structure ceramsite was placed in an 80°C drying oven and dried to constant weight. The dried core-shell structure ceramsite (sealed and cooled to room temperature) was then immersed in water (immersion time was 1h, 3h, 6h, 12h, and 24h, respectively) to test its mass change. The arithmetic mean of the three measured values was taken as the experimental result. The water absorption rate was calculated according to formula III:
[0101] w a =(m0-m1) / m1×100 Formula III;
[0102] w a ——Water absorption rate, in %;
[0103] m0——mass of immersed sample, in grams (g);
[0104] m1——mass of dried sample, in grams (g).
[0105] (4) Biochar ratio
[0106] Biochar itself has high carbon stability, so when used in concrete, it can be regarded as a carbon sequestration measure. The higher the biochar content in concrete, the greater the corresponding carbon sequestration amount. According to the absolute volume method of JGJ55-2011 "Ordinary Concrete Mix Design Code", concrete containing ceramsite was prepared using core-shell ceramsite. The calculation of 1m 3 The volume of core-shell ceramsite in ceramsite-containing concrete is 0.66m 3 , can be calculated according to the formula 1m 3 The content of biochar in ceramsite-containing concrete is specifically shown in Formula IV:
[0107]
[0108] V 生物炭 - Biochar accounts for the volume of ceramsite-containing concrete;
[0109] V 陶粒生物炭 ——The volume of biochar in core-shell ceramsite;
[0110] V 陶粒外壳 ——The volume of the outer shell in core-shell structure ceramsite.
[0111] (5) Microstructure analysis of core-shell structure ceramsite
[0112] The core-shell structured ceramsite was cut and polished, and after drying, the interface surface morphology was observed using a field emission environmental scanning electron microscope.
[0113] Characterization and test results:
[0114] Figure 6 The chart below shows the test results of cylinder compressive strength and bulk density of core-shell ceramsite. Figure 7 The results of the water absorption test of the core-shell structure ceramsite are shown in Table 4. The results show that the bulk density of the core-shell structure ceramsite prepared in Examples 1 to 8 is 658.7 to 817.0 kg / m 3 , meeting the GBT17431 national standard for 700-900 grade ceramsite; the cylinder compressive strength is 4.8-10.9 MPa, meeting the GBT17431 national standard for 800 grade; the 1-hour water absorption rate is 16.1%-26.2%, significantly reducing the water absorption rate of biochar; and the volume percentage of biochar in concrete is 25-36%. Comparative Examples 1-3, which use 100% cement as the outer shell, have a relatively high bulk density and use a large amount of cement under the same conditions, making them unsuitable for widespread application and not meeting the requirements of green and low-carbon development.
[0115] Table 4 Physical property test results of core-shell structure ceramsite in Examples 1 to 8 and Comparative Examples 1 to 3
[0116]
[0117]
[0118] Figure 8 The cross-sectional physical image and three-dimensional scanning image of the core-shell structure ceramsite prepared in Example 1, wherein the upper part is the cross-sectional physical image and the lower part is the three-dimensional scanning image. The results show that the biochar is completely wrapped by the shell, thereby solving the problem of low incorporation amount of biochar in concrete due to its high water absorption rate.
[0119] Figure 9 This is the SME diagram of the interface between the core and the shell in the core-shell structure ceramsite prepared in Example 1. The results show that the steel slag powder and the glass powder excite each other, and the reaction ring around the glass powder is the hydration product under the mutual excitation.
[0120] Figure 10 This is a physical picture of the core-shell structure ceramsite prepared in Example 1. Figure 11 This is a physical picture of the core-shell structure ceramsite prepared in Example 2. Figure 12 This is a physical picture of the core-shell structure ceramsite prepared in Example 3. Figure 13 This is a physical picture of the core-shell structure ceramsite prepared in Example 4. Figure 14 This is a physical picture of the core-shell structure ceramsite prepared in Example 5. Figure 15This is a physical picture of the core-shell structure ceramsite prepared in Example 6; the results show that the outer shell of the core-shell structure ceramsite prepared in each example completely wraps the biochar.
[0121] From the above results, it can be seen that the present invention uses biochar as the core and steel slag powder and glass powder as the shell to prepare core-shell structured ceramsite with high strength, light weight and high carbon fixation efficiency, which solves the problem of steel slag and glass solid waste utilization and realizes the carbon fixation function of a large amount of biochar. The core-shell structured ceramsite can be used as lightweight aggregate.
[0122] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A core-shell ceramsite, comprising a core and a shell wrapped around the core, wherein the core is biochar, and the shell is prepared from raw materials including steel slag powder, glass powder, and cement, wherein the total mass content of the steel slag powder and glass powder in the shell is greater than 50%.
2. The core-shell structure ceramsite according to claim 1, wherein The core-shell structure ceramsite has a cylinder pressure strength of 4.8-10.9 MPa and a bulk density of <900 kg / m 3 .
3. The core-shell structure ceramsite according to claim 1, wherein The steel slag powder has a particle size D90 ≤ 20 μm, a free calcium oxide content of 0 to 6 wt%, and a calcium hydroxide content of 0 to 8 wt%; The particle size D90 of the glass powder is ≤45 μm, and the glass powder is obtained by grinding waste glass; The cement is ordinary Portland cement.
4. The core-shell structure ceramsite according to claim 1, wherein The thickness of the shell is 1 to 2 mm; the particle size of the biochar is 2.36 to 4.75 mm, and the bulk density is 300 to 600 kg / m 3 , the cylinder pressure strength is 1.5~5MPa.
5. The core-shell structure ceramsite according to any one of claims 1 to 4, characterized in that: The mass ratio of the steel slag powder to the glass powder is 3:6-8, the mass ratio of the total mass of the steel slag powder and the glass powder to the cement is 7-9:1-3; the volume ratio of the raw materials for preparing the shell to the biochar is 0.5-2:
1.
6. The method for preparing the core-shell structure ceramsite according to any one of claims 1 to 5, comprising the following steps: Firstly mixing steel slag powder, glass powder and cement to obtain shell raw materials; performing a second mixing of the shell raw material and biochar to obtain a biochar mixture; The biochar mixture is mixed with water for a third time to obtain prefabricated ceramsite; The prefabricated ceramsite is cured and formed to obtain the core-shell structure ceramsite.
7. The preparation method according to claim 6, characterized in that The biochar includes completely dry biochar or saturated surface dry biochar; when the biochar is completely dry biochar, the mass ratio of the water to the shell raw material is 0.2 to 0.4:1; when the biochar is saturated surface dry biochar, the mass ratio of the total mass of the water and the water in the saturated surface dry biochar to the shell raw material is 0.2 to 0.4:
1.
8. The preparation method according to claim 6, characterized in that The first mixing, the second mixing and the third mixing are carried out in a rotary granulator; the conditions for the first mixing include: a rotation rate of 32 to 48 r / min, a rotation angle of 40 to 45°, and a mixing time of 4 to 6 min; the conditions for the second mixing include: a rotation rate of 32 to 48 r / min, a rotation angle of 40 to 45°, and a mixing time of 1.5 to 2.5 min; the conditions for the third mixing include: a rotation rate of 16 to 24 r / min, a rotation angle of 40 to 45°, and a mixing time of 20 to 30 min.
9. The preparation method according to any one of claims 6 to 8, characterized in that The curing temperature is 80°C and the curing time is 3 days.
10. Use of the core-shell structure ceramsite according to any one of claims 1 to 6 or the core-shell structure ceramsite prepared by the preparation method according to any one of claims 7 to 9 in lightweight carbon-fixing aggregate concrete.
Citation Information
Patent Citations
Preparation method of solid waste solidified river sediment heavy metal and unfired shell-wrapped ceramsite and river sediment-based unfired shell-wrapped ceramsite
CN116375378A
Lightweight core-shell aggregate and concrete
CN118652066A
Steel slag powder composite waste glass mortar and preparation method thereof
CN119019136A
Negative carbon lightweight aggregate concrete mix proportion design method and preparation method
CN119430771A
Artificial lightweight aggregate and production thereof
JP1998231152A
Cited By
Preparation method of artificial fish reef concrete
CN122145103A